Persistent connections with as a method of distribution of the load on the WEB-server - Жуков, І. А.; Кравець, І. М. (Problems of Informatization and Control, 2008)
The cluster system, which consists of WEB-servers, segmented database and load-balancer, is created. A model and specific configuration is offered for the use of specialized «proxy-servers», that substantially distributionloading for bases given by persistent connections. Experimental results led to efficiency of the use of persistent connections